Offshore Technology Conference 2005
DOI: 10.4043/17548-ms
|View full text |Cite
|
Sign up to set email alerts
|

New Technology Applications to Extend Field Economic Life by Creating Uniform Flow Profiles in Horizontal Wells: Case Study and Technology Overview

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractHorizontal wells on a global basis continue to serve as a primary well type for improving recovery efficiency, increasing reservoir drainage area, delaying water and gas coning, and increasing production rate. However, in longer, highly deviated and horizontal wells, non-uniform flow profiles can result in premature water or gas breakthrough, screen plugging, and erosion which can shorten well life and decrease well profitability. This paper describes histori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This technique uses preventive actions throughout a well's life to regulate water production. Using the newest inflow control systems, such as Inflow Control Device [11,12], Autonomous Inflow Control Device [13], Inflow Control Valves [15,17], and Intelligent wells [16], together with zonal isolation according to reservoir parameters, can assist prevent water penetration into a wellbore. This completion approach can increase a well's life, limit well intervention, produce hydrocarbons effectively, and reduce water output, making it inexpensive.…”
Section: Resultsmentioning
confidence: 99%
“…This technique uses preventive actions throughout a well's life to regulate water production. Using the newest inflow control systems, such as Inflow Control Device [11,12], Autonomous Inflow Control Device [13], Inflow Control Valves [15,17], and Intelligent wells [16], together with zonal isolation according to reservoir parameters, can assist prevent water penetration into a wellbore. This completion approach can increase a well's life, limit well intervention, produce hydrocarbons effectively, and reduce water output, making it inexpensive.…”
Section: Resultsmentioning
confidence: 99%
“…of system failure [26]. The ICD is more capable of producing low flowrate fluid formations and including artificial lift in the form of gas lift to produce remaining reserves for maximum oil recovery in a well.…”
Section: Completion Strategy For Different Reservoir Propertiesmentioning
confidence: 99%
“…It was completed with 279 joints of SAS equipped with ICDs. The numerical simulation indicated that a "stair step" arrangement with the highest strength ICD (3.2 bar) at the heel section of the well and a SAS without ICDs toward the toe of the well is the optimum completion design 14 . Annular isolation with External Casing Packers (ECPs) to prevent flow along the length of the formation face was not employed.…”
Section: Icd With Sas In Horizontal Wellsmentioning
confidence: 99%
“…Many of the reported ICD applications included one of these packer types 17,19,20,22 . The Z-253 well was completed in Zuluf Field, offshore Saudi Arabia, utilized four Mechanical ECPs in conjunction with single strength channel-type ICD to segment a 2200 ft-long wellbore 14,15 . The placement of the ECPs was based on the permeability of each hole section.…”
Section: 2mentioning
confidence: 99%